Disfunção erétil : um marcador precoce de doença aterosclerótica coronariana - Andrade, Weslley Santiago (2011)
Objective: To investigate the association between coronary atherosclerosis (CAD) and erectile dysfunction (ED) in men undergoing coronary angiography, according to the complexity of the CAD and the severity of ED and the power of the abridged five item version of the questionnaire International Index of Erectile Function (IIEF) in the diagnosis of CAD. Patients and Methods: A case study - control, conducted between January to November 2010 which evaluated 132 consecutive patients were submitted to coronary angiography divided into two groups according to presence (group 1, composed of 86 patients) or absence (group 2 - composed of 46) of CAD, which was defined by lesions with an area of stenosis greater than or equal to 50% of the diameter of the coronary vessel. Patients underwent IIEF-5 to assess the presence, degree and how long ago were suffering from erectile dysfunction and then was made the measure of the Syntax score for assessing the complexity of coronary lesions. Results: There is an independent association between ED and CAD with an odds ratio of 40.6 (95% CI 14.3 to 115.3 p <0.0001). The cutoff point 21, the IIEF-5 had a sensitivity of 91.2%, specificity of 78.3% and 87% accuracy for diagnosis of CAD. The ED was already present in patients with a period about twice as large (38.8 ± 2.3 months) than in patients without CAD. Patients without erectile dysfunction Syntax average score was 6.3 ± 3.5 while those who had moderate to severe erectile dysfunction was 39.0 ± 11.1. Conclusion: There is an independent association between ED and CAD and ED should be considered an early marker of CAD as well as its complexity and the questionnaire IIEF-5 has exceptional ability to diagnose it.